2023
DOI: 10.3389/fenvs.2023.1117427
|View full text |Cite
|
Sign up to set email alerts
|

Post-fire recovery of soil organic carbon, soil total nitrogen, soil nutrients, and soil erodibility in rotational shifting cultivation in Northern Thailand

Abstract: The hill tribes in Thailand traditionally depend on rotational shifting cultivation (RSC). However, insufficient understanding remains on post-fire soil properties and soil erodibility (k-values) with fallow years. To address this gap, the levels of soil organic carbon (SOC), soil total nitrogen (STN), soil nutrients, and soil erodibility after fire in RSC were investigated. Topsoil (0–10 cm) samples from sites with 4 (RSC-4Y), 5 (RSC-5Y), and 7 (RSC-7Y) fallow years in Chiang Mai Province, northern Thailand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…In Northern Thailand, rotational shifting cultivation (RSC) is a traditional farming practice among the inhabitants of mountainous regions (Arunrat et al, 2022b). RSC involves managing fallow cycles where one area is temporarily cultivated and subsequently left fallow to allow vegetation and soil fertility to recover, while the farmers move on to another area (Arunrat et al, 2023a). Fire is utilized as a land preparation tool during the conversion process, altering soil characteristics depending on the severity and intensity of the burn (Caon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Northern Thailand, rotational shifting cultivation (RSC) is a traditional farming practice among the inhabitants of mountainous regions (Arunrat et al, 2022b). RSC involves managing fallow cycles where one area is temporarily cultivated and subsequently left fallow to allow vegetation and soil fertility to recover, while the farmers move on to another area (Arunrat et al, 2023a). Fire is utilized as a land preparation tool during the conversion process, altering soil characteristics depending on the severity and intensity of the burn (Caon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Red, burned site; Blue, unburned site. cause the death of soil organisms but also change the availability of organic matter, nutrients, and pH (De Marco et al, 2005;Capogna et al, 2009;Pellegrini et al, 2022;Arunrat et al, 2023;Zhang et al, 2023). There are three types of strategies soil organisms can adopt to survive forest fires: flee, hide, and protect.…”
Section: Discussionmentioning
confidence: 99%
“…Older fallow fields accumulate more leaf litter and other organic debris from above and below-ground biomass (Murovhi et al, 2012). In addition, the roots of weeds and grasses are a significant source of OM in the surface layer (Arunrat et al, 2023). This finding is consistent with Sharma et al (2022), who reported that higher OM inputs from persistent vegetation cover in older fallow fields contribute to the higher OC content compared to 3) suggests that it is rich in OM and undergoes more organic acid production during decomposition processes, which is consistent with Hong et al (2019).…”
Section: Effect Of Fallow Periods On Soil Properties and Soil Surface...mentioning
confidence: 99%
“…In northern Vietnam, Dung et al (2008) estimated that the recovery of nitrogen and phosphorus would require more than 30 years and more than 6 years, respectively. In northern Thailand, Arunrat et al (2023) observed that SOC and STN stocks had not reached pre-fire levels even after 2 years had passed. Meanwhile, a longer cycle duration allowed the germination of weed seeds and regrowth, which enhances the recovery of soil nutrients and reduces soil loss (Figure 7).…”
Section: Effect Of Fallow Periods On Soil Properties and Soil Surface...mentioning
confidence: 99%